MODEL PEMBIAYAAN PENDIDIKAN DI SEKOLAH: MENUJU KEBERLANJUTAN DAN INKLUSIVITAS PENDIDIKAN - Sahda Masyhura (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to investigate and analyze education financing models in schools with a focus on efforts towards educational sustainability and inclusiveness. The method used in this research is a literature review, where literature related to education financing, sustainability and educational inclusivity will be analyzed in depth. This research seeks further understanding of innovative and effective financing models to ensure the sustainability of the education system, as well as to increase the inclusiveness of educational access. In carrying out the literature review method, this research will explore various theories and concepts related to education financing, involving various approaches that have been adopted by schools in various contexts. An in-depth analysis will also be carried out on efforts to achieve educational sustainability, including financial, social and environmental aspects that can influence educational sustainability. It is hoped that the results of this research will provide valuable insights for education policy makers, schools and other related parties to develop more sustainable and inclusive financing models. Thus, this research can make a positive contribution to improving the education system to be better and fairer.